Assessing The Feasibility of An Integrated Islamic School: A Case Study of Mustafa School In East Jakarta - Gilang Acmalta (International Journal of Science and Environment (IJSE), 2026)
The screening of the viability of educational ventures in developing economies poses special challenges that demand the combination of many analytical perspectives. Although strategic management and financial evaluation frameworks are two distinct fields, little study has shown how the two frameworks are systematically combined to apply in educational entrepreneurship. This paper presents and empirically validates an overall feasibility model incorporating resource-based perspective (VRIO analysis), market validation approach, capital budgeting techniques and multi-scenario risk analysis. The model is used to assess the proposal to establish an integrated Islamic school in East Jakarta, Indonesia that is a booming education market where the network of JSIT schools has grown by 100 to more than 2,300 schools since 2003. Based on the mixed-method approach and purposive sampling of five information-rich cases and secondary data gathering within the government statistics, the study indicates the use of the framework in four dimensions of feasibility. Results indicate: (1) market feasibility was confirmed by the use of thematic analysis, which indicated that 100 percent of respondents cited commute burden as a critical pain point with 80 percent high purchase intent; (2) organizational feasibility was confirmed by the use of VRIO-identified sustained competitive advantages debt-free capital structure and secured strategic location; (3) financial feasibility was confirmed by NPV of IDR 8.93 billion, IRR of 26.28 percent exceeding 14 percent WACC, 4.83-year The study is a contribution of an operationalizable integrated model between theory of strategic management and financial evaluation practice on assessment of educational venture in new markets.